Strong cation- and zwitterion-exchange-type mixed-mode stationary phases for separation of pharmaceuticals and biogenic amines in different chromatographic modes - Wolrab, Denise; Fruehauf, Peter; Kolderova, Natalie; Kohout, Michal (Elsevier Science BV, 2021)
A set of new mixed-mode ion-exchange stationary phases is presented. The backbone of organic selectors is formed by a linear hydrocarbon chain, which is divided into two parts of various lengths by a heteroatom (oxygen or nitrogen). In all studied cases, there is a sulfonic acid moiety as the terminal group. Therefore, selectors bearing oxygen gave rise to strong cation ion-exchange stationary phases, while selectors with an embedded nitrogen atom (inducing a weak anion exchange capacity) were used to create zwitterion ion-exchange stationary phases. The new mixed-mode stationary phases were chromatographically evaluated in high performance liquid chromatography (HPLC) and supercritical fluid chromatography (SFC) using isocratic elution conditions to disclose their chromatographic potential. In HPLC mode, aqueous-rich reversed phase chromatography, acetonitrile-rich hydrophilic interaction liquid chromatography and methanolic ion-exchange chromatography mobile phases were employed. In these chromatographic modes, retention factors and selectivity values for a test set of basic and zwitterionic analytes were determined. The results were compared and principal component analysis for each chromatographic mode was performed. For all chromatographic modes, the component 1 in the principal component analysis reflected the elution order. The application of different mobile phases on a particular column resulted not only in variation in retention, but also in modified selectivity, and different elution order of the analytes. The orthogonality of the elution order depending on the employed mobile phase conditions was especially reflected for structurally closely related analytes, such as melatonin and N-acetyl-serotonin, tryptamine and serotonin or noradrenalin and octopamine. However, ion-exchange interactions remain the main driving force for retention. From all investigated stationary phases, the SCX 2 (C5-linker and C4-spacer) seems to be the best choice for the separation of basic analytes using different mobile phase conditions. (C) 2020 Elsevier B.V. All rights reserved.
Silné stacionární fáze se smíšeným režimem pro kationtovou a zwitteriontovou výměnu pro separaci léčiv a biogenních aminů v různých chromatografických režimech
Keywords: ion-exchange stationary phases; mixed-mode stationary phases; liquid chromatography; supercritical fluid chromatography; biogenic amines; iontoměničová stacionární fáze; stacionární fáze ve smíšeném režimu; kapalinová chromatografie; superkritická fluidní chromatografie; biogenní aminy